Crossing quartiles: Improving time to theatre for patients with hip fractures in a large UK district general hospital; A quality improvement report. Issue 11 (November 2021) - Anthony, Christopher; Malaj, Marta; Lokanathan, Prashan; Murgatroyd, James; O'Connor, Patrick
Highlights: Improving continuity of care in hip fracture patients can improve compliance with the best practice tariff Abstract: Background: Neck of femur fractures are common injuries in the elderly population and carry significant morbidity and mortality. The introduction of a Best Practice Tariff (BPT) in 2010 laid out the criteria for optimising hip fracture care. These outcomes are audited annually by the National Hip Fracture Database. Meeting all six key targets attracts a financial uplift for each patient; one of these criteria is for an operation within 36 hours of admission. Local problem: A large district general, seeing on average 551 hip fracture patients a year. In 2017, the trust was ranked 152/160 in England for meeting the 36-hour target to surgery, although theatre capacity was sufficient. The average time to theatre was 43.68 hours, significantly above the national average. BPT was only achieved in 45.7% of cases. Method: In January 2018 an anaesthetic 'hot week' was introduced with the same anaesthetist responsible for the hip fracture lists to allow for continuity of care and timely identification of potential delays to surgery. Further responsibilities include attending trauma meeting, liaising with the orthopaedic and the orthogeriatric teams, and advising on medical optimisation of patients for theatre. Results: Comparing data for 2017 (pre-intervention) with 2018 (post-implementation), the following results in key measures were noted: Surgery within 36 hours increased from 54% to 87.5% of patients. Mean time to surgery fell from 43.68 hours to 25.11 hours. Attainment of BPT targets increased from 45.7% to 84%. Trust ranking went from 152 nd to 20 th for time to surgery and from 131 st to 18 th for meeting BPT. Rescheduled operations went from 126 to 31. As a result, mean length of stay reduced by 5.1 days. Mortality remained unchanged. Conclusion: Implementation of an anaesthetic 'hot week' may help trusts improve times to theatre where sufficient theatre capacity is already in place.